3D Printing and Bioprinting in MEMS Technology - Chua, Chee Kai (2017)
3D printing and bioprinting have advanced significantly in printing resolution in recent years, which presents a great potential for fabricating small and complex features suitable for microelectromechanical systems (MEMS) with new functionalities. This special issue aims to give a glimpse into the future of this research field.